1997
DOI: 10.1148/radiology.204.2.9240556
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic breast biopsy of clustered microcalcifications with a directional, vacuum-assisted device.

Abstract: The success rate with the traditional 14-gauge, core-biopsy, multiple-pass technique was compared with that of a directional vacuum-assisted device in sampling calcification clusters in the breast. Of the 130 focal calcification clusters sampled with the multiple-pass technique, 12 clusters (9.2%) had no particles depicted on radiographs of the specimen. Specimens from all 106 (100%) clusters sampled with the directional, vacuum-assisted instrument contained calcifications at radiography. The directional, vacu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
3
5

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 0 publications
6
47
3
5
Order By: Relevance
“…Still, the number of included ADH cases was insufficient to make a reliable comment on underdiagnosis. In previous studies, underestimation rates for carcinoma ranged between 18% and 20% (9,(27)(28)(29)(30)(31). Our results are comparable with the literature for carcinoma underestimations using DCIS.…”
Section: Discussionsupporting
confidence: 88%
“…Still, the number of included ADH cases was insufficient to make a reliable comment on underdiagnosis. In previous studies, underestimation rates for carcinoma ranged between 18% and 20% (9,(27)(28)(29)(30)(31). Our results are comparable with the literature for carcinoma underestimations using DCIS.…”
Section: Discussionsupporting
confidence: 88%
“…This technique uses only one puncture, with the probe of the device remaining within the breast, at the site of interest, throughout the sampling. Meyer et al (8) showed 90.8% of microcalcifications in samples obtained using standard automated needle devices compared with 95%-100% of microcalcifications in samples extracted by the vacuum-assisted device (19,20). Accordingly, in our series, microcalcifications were identified in specimen radiographs of 98.5% of lesions.…”
Section: Discussionmentioning
confidence: 44%
“…It is particularly advantageous in the assessment of calcified lesions (7)(8)(9)(10)(16)(17)(18). This technique uses only one puncture, with the probe of the device remaining within the breast, at the site of interest, throughout the sampling.…”
Section: Discussionmentioning
confidence: 99%
“…A failure occurred only in one case with the EnCor ® probe. However, this finding cannot be attributed to the system used, since failure rates between 0 and 5 % with Mammotome ® system in previous studies have been described [21][22][23].…”
Section: Discussionmentioning
confidence: 80%